Genomic islands of divergence in the Yellow Tang and the Brushtail Tang Surgeonfishes. Issue 17 (2nd August 2018) - Bernardi, Giacomo; Nelson, Peter; Paddack, Michelle; Rulmal, John; Crane, Nicole
Abstract: The current ease of obtaining thousands of molecular markers challenges the notion that full phylogenetic concordance, as proposed by phylogenetic species concepts, is a requirement for defining species delimitations. Indeed, the presence of genomic islands of divergence, which may be the cause, or in some cases the consequence, of speciation, precludes concordance. Here, we explore this issue using thousands of RAD markers on two sister species of surgeonfishes (Teleostei: Acanthuridae), Zebrasoma flavescens and Z. scopas, and several populations within each species. Species are readily distinguished based on their colors (solid yellow and solid brown, respectively), yet populations and species are neither distinguishable using mitochondrial markers (cytochrome c oxidase 1), nor using 5193 SNPs (pairwise Φst = 0.034). In contrast, when using outlier loci, some of them presumably under selection, species delimitations, and strong population structure follow recognized taxonomic positions (pairwise Φst = 0.326). Species and population delimitation differences based on neutral and selected markers are likely due to local adaptation, thus being consistent with the idea that these genomic islands of divergence arose as a consequence of isolation. These findings, which are not unique, raise the question of a potentially important pathway of divergence based on local adaptation that is only evident when looking at thousands of loci. Abstract : Populations and species delimitations have traditionally been proposed based on a limited number of molecular markers. Here, we show that the use of thousands of loci, including outlier loci, which are presumed to be under selective constraints, helps define such delimitations, thus refining our understanding of species boundaries.